Seasonal variability in the pregnancy rate of women undergoing Intracytoplasmic Sperm Injection Technique - Leila Noory; Najmeh Nooryrad; Mohsen Pourghasem; Fezzeh Hashemi; Hamid Shafi (Babol University of Medical Sciences, 2016)
Background: It is evident that seasonal changes can affect the function of animal reproductive system, and human reproductive system is no exception in this regard. These changes can be attributed to the effect of light during different seasons, especially on the reproductive system of females. There are, on the other hand, many reports that indicate no significant relation between seasons and the fertility rate of pregnancy and implantation. The aim of the present study was to clarify different views in case of seasonal effects on the rate of fertility and pregnancy. Methods: The present study was conducted on 1287 couples at the Infertility Center, Babol University of medical sciences. The couples received embryos after intracytoplasmic sperm injection (ICSI) was included in the study. The participants were divided into five groups based on their age (18-23, 24-28, 29-33, 34-38 and 39-43). The level of significance was set at p < 0.05. Results: Women who received embryos were between the age range of 18 and 43. It should be mentioned that the range of pregnancy in different seasons was different,  and that the maximum number of pregnancies happened in autumn. Most pregnancies happened in 28 to 33 year olds. The quality of embryos was better in autumn than other seasons. Conclusion: The results indicated that seasonal changes can have an effect on the pregnancy rate through ICSI technique.